Simultaneous enrichment of aluminium and lead with cupferron on activated carbon for determination in milk and fruit juices by atomic absorption spectrometry - Yaman, M (Springer Wien, 1998)
An enrichment method has been modified for the determination of Al in animal milk and fruit juices by flame atomic absorption spectrometry (FAAS). The samples were digested by wet ashing. 8-Hydroxyquinoline and cupferron were used as complexing reagents for adsorption of the Al complexes on activated carbon. The pH values for maximum recovery of Al were in the ranges 4.4-6.0 for cupferron and 8.0-9.0 for oxine, The relative standard deviation was 4% for an aluminium concentration of 120 mu g L-1 using cupferron. Optimum conditions for lead enrichment were taken from previous work on the cupferron-activated carbon enrichment method. The optimized procedure was applied to the determination of Al and Pb in animal milk and fruit juices by FAAS. Simultaneous enrichment of these two elements was achieved at the same pH.
Keywords: aluminum; lead; preconcentration on activated carbon; atomic absorption spectrometry; fruit juices; animal milk; cupferron; oxine